Washington View: No hope from Betsy DeVos. (March 2019) - Ferguson, Maria
Maria Ferguson considers the problems with Betsy DeVos' efforts to roll back regulations of for-profit colleges and universities and dismantle civil rights protections for students. In both cases, the moves fly in the face of evidence and demonstrate a desire to deconstruct efforts to fully protect students .